2015
DOI: 10.1136/bmjopen-2014-006913
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of cancer research in South Africa: study protocol

Abstract: IntroductionCancer is an important and growing public health burden in South Africa (SA). Over the past few decades, there has been considerable scientific activity in cancer in SA. However, there has been limited analysis of cancer scientific publications. In this paper, we present a protocol for bibliometric analysis of cancer research conducted in SA.Methods and analysisA comprehensive search of the journal databases PubMed, SCOPUS, Web of Science and EBSCO will be conducted to identify and retrieve data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Bibliometric analysis is a relatively thorough method of information science research which combines science with statistical mathematical methods to quantitatively analyze information and knowledge. 1 With a bibliometric analysis, it is possible to associate the impact and growth of the scientific literature, the processes within academic fields, and the knowledge trends which can help to create specific public healthcare plans. 2 A bibliometric analysis allows researchers to recognize key study topics and investigate updated ideas in a given field.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is a relatively thorough method of information science research which combines science with statistical mathematical methods to quantitatively analyze information and knowledge. 1 With a bibliometric analysis, it is possible to associate the impact and growth of the scientific literature, the processes within academic fields, and the knowledge trends which can help to create specific public healthcare plans. 2 A bibliometric analysis allows researchers to recognize key study topics and investigate updated ideas in a given field.…”
Section: Introductionmentioning
confidence: 99%
“…Biomedical research publication has been frequently used as an index for assessing the worldwide scientific productivity in a specific field. [ 18 , 20 , 26 ] Bibliometric analyses have been utilized to assess the worldwide scientific productivity in several biomedical fields. [ 13 , 19 , 25 , 27 , 28 ] Recently, Huang et al performed a citation analysis focusing on the back pain, which was published in Spine .…”
Section: Discussionmentioning
confidence: 99%
“…From hotspot analysis and keyword co-word network evolution diagram, the research field of emerging technologies in cancer is found to present diversified topics. Disease hotspots (e.g., cancer, breast cancer, and prostate cancer) reflect the major diseases that have been of concern to scholars in this field worldwide in this century 42,43. Hotspots in technologies, such as categorization, robotics, machine learning, data mining, prediction, support vector machines, and feature selection, reflect that the research field of emerging technologies in cancer has been prominent since the beginning of this century.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%